The Influence of Hello Book Media on Early Childhood Language Skills - Dwiyanti, Linda; Khan, Rosa Imani (Jurnal Pendidikan Indonesia, 2020)
Children who have difficulty expressing their wants and needs are more likely to be helped and fail to gain independence. Providing stimulation to foster communication skills starting from an early age through play and media activities. This study aims to analyze the effect of the Hello Book media on early childhood language skills. This type of research is a Quasi Experiment (quasi-experiment). The population in this study were students of group B of two Kindergarten Institutions. The data collection technique uses observation to determine the level of development of language skills. The hypothesis test used is the Independent t-test parametric statistical test. According to the calculation results obtained t = -4,303 with a sig value. = 0.0001. The difference in the mean value between the experimental group and the control group was 2,150. Thus, it can be concluded that the use of Hello Book media in learning has a positive and significant effect on children's language skills in Kindergarten.